2007
DOI: 10.3111/200710119134
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of contrast-induced nephropathy: implications for prevention strategies

Abstract: SUMMARY Contrast-induced nephropathy (CIN) is the third most common cause of hospital-acquired acute renal failure. There is increasing evidence that CIN has a significant adverse impact on patient morbidity and mortality. The objective of this study was to estimate the in-hospital and 1-year direct healthcare costs related to CIN. Using the values obtained from the literature review, a decision analytic model was developed to estimate the in-hospital and 1-year costs of CIN. Patients who develop CIN are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 21 publications
0
65
0
1
Order By: Relevance
“…In a series of 200 patients undergoing PCI for acute MI, patients who developed contrast-induced AKI had a longer hospital stay, a more complicated clinical course, and a significantly increased risk of death compared to those without contrast-induced AKI [25]. A recent economic analysis of the direct costs associated with contrast-induced AKI showed that the average additional cost was USD 10,345 for the hospital stay and USD 11,812 for 1 year [29]. The major determinant of the increased costs associated with contrast-induced AKI was the cost of the longer initial hospital stay.…”
Section: Epidemiology and Prognostic Implications Of Contrast-inducedmentioning
confidence: 99%
“…In a series of 200 patients undergoing PCI for acute MI, patients who developed contrast-induced AKI had a longer hospital stay, a more complicated clinical course, and a significantly increased risk of death compared to those without contrast-induced AKI [25]. A recent economic analysis of the direct costs associated with contrast-induced AKI showed that the average additional cost was USD 10,345 for the hospital stay and USD 11,812 for 1 year [29]. The major determinant of the increased costs associated with contrast-induced AKI was the cost of the longer initial hospital stay.…”
Section: Epidemiology and Prognostic Implications Of Contrast-inducedmentioning
confidence: 99%
“…[7][8][9] Finally, CI-AKI results in prolonged hospitalizations and additional costs. 10 To estimate the preprocedural risk of CI-AKI in interventional cardiology is of crucial importance, especially in patients with STEMI, whose renal function cannot yet be assessed accurately at the time of clinical presentation. Identifying patients at risk has a direct effect in targeting prophylactic interventions.…”
mentioning
confidence: 99%
“…Its occurrence has been linked to late cardiovascular events after percutaneous coronary intervention (such as myocardial infarction), bleeding requiring transfusion, and vascular complications. As a consequence of more serious adverse events, the in-hospital stay is longer with an estimated US$10,000 to US$12,000 added to the final bill during the first year (Subramanian et al, 2007).…”
Section: Negative Positive Coronary Angiography Negative Positivementioning
confidence: 99%